If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ln(x + -7) = 4 Reorder the terms: 2ln(-7 + x) = 4 (-7 * 2ln + x * 2ln) = 4 (-14ln + 2lnx) = 4 Solving -14ln + 2lnx = 4 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -4 + -14ln + 2lnx = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -14ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + -7ln + lnx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -7ln + lnx)' equal to zero and attempt to solve: Simplifying -2 + -7ln + lnx = 0 Solving -2 + -7ln + lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -7ln + 2 + lnx = 0 + 2 Reorder the terms: -2 + 2 + -7ln + lnx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -7ln + lnx = 0 + 2 -7ln + lnx = 0 + 2 Combine like terms: 0 + 2 = 2 -7ln + lnx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4x+30=12x-15 | | 13-9x=198-44x | | 4k^2-9k-5=0 | | 2(4x-1)=22 | | 11x-31=7x+4 | | y-1/y-3=(y-1/y+5)+1 | | 17/3x+3/5=8/3x | | X^1/3-2=0 | | 2x^4-2=160 | | 6x-13=3(2x+9) | | y=-4/x+3 | | 8t-26=-30 | | 21/25=x/75 | | 7y=2+5x | | 2v+26=6v+30 | | 4(3y-2)+2(3y-2)= | | (u-2)(4+4)= | | 13=0-45x+9 | | -34-2x=11-7 | | 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 |